PENGARUH LEMBAR KERJA SISWA BERBASIS PQ4R TERHADAP HASIL BELAJAR IPA FISIKA KELAS VIII SMPN 1 LINGGO SARI BAGANTI - Nessa Anugra Rahmi (PILLAR OF PHYSICS EDUCATION, 2013)
Learning in school still not involve active participation of students. so that student learning outcomes in the cognitive domain is still low, because many students are simply stunned and did not participate in the study, which is done by applying alternative based LKS PQ4R provide opportunities for students to interact, engage actively in learning activities. This study aimed to investigate the effect of LKS PQ4R Based on the results of science learning physics class VIII SMP N 1 Linggo Sari Baganti. Type of research is quasi-experimental research by design "Randomized Control Group Design Only". The study population was a student of class VIII SMP N 1 Linggo Sari Baganti enrolled in Academic Year 2012/2013 consists of 5 classes. Cluster sampling with random sampling techniques. As a sample drawn 5 class VIII as an experimental class VIII and class 4 as the control class. Research instruments such as achievement test, observation format affective and psychomotor assessment sheet. The data obtained were analyzed using two similarity test average on the real level of 0.05. Based on the analysis of data, study results obtained on the three domains, namely cognitive, affective, and psychomotor. It can be concluded that there is significant influence between students who use worksheets based PQ4R with the use of existing school worksheets on learning outcomes of students' science Physics.   Keywords: Student Worksheet, PQ4R, Science, Learning Outcome